Identification of Eyes At Risk for Severe Retinopathy of Prematurity (ROP) by Third Year Ophthalmology Residents in a Tertiary Hospital - B. Iguban Eleonore; H. Arroyo Milagros (Journal of Ophthalmic Science, 2018)
Objective: The aim of the present study is to determine the efficiency of third year ophthalmology residents from a tertiary hospital in performing preliminary retinal examination to identify eyes at risk retinopathy of prematurity on the basis of retinal fundus findings up to International Classification of Retinopathy of Prematurity (ICROP) Zone II. Methods: This is a single-center, cross-sectional, prospective comparative research conducted from June to October 2015 at a tertiary training hospital in the Philippines. All infants referred for retinopathy of prematurity screening within the study period where included. The presence of retinal vessel dilatation and tortuosity were identified by third year ophthalmology residents using indirect funduscopy. The residents’ fundus findings were then compared to that of a retina consultant who is proficient in the diagnosis and management of retinopathy of prematurity (ROP). The Kappa index was used to rate inter-observer agreement. The correlation between ROP risk factors and the presence of abnormal retinal vessels were assessed using odd ratio computations. Fisher’s exact test was used to determine the correlation between retinopathy of prematurity and the presence of retinal dilatation and tortuosity. The McNemar’s test was also applied to determine significant differences in the retinal findings of the consultant and ophthalmology residents. Results: A total of 82 eyes of 41 premature infants were evaluated to determine if retinal findings observed by ophthalmology residents were comparable to that of a retina consultant. Odds ratios show that age of gestation, birth weight, and history of blood transfusion are significantly associated with the presence of retinopathy of prematurity. Retinal vessel tortuosity and dilatation are also more common among infants diagnosed with retinopathy of prematurity. There was no significant difference between the retinal vascular findings of the retina consultant and the third year ophthalmology resident in terms of identifying retinal vessel dilatation and tortuosity (P < 0.05). Conclusion: After sufficient and in-depth ophthalmology training, third year ophthalmologists, who will be general ophthalmologists in the future, can reliably identify eyes at risk for severe retinopathy of prematurity on the basis of retinal vascular dilatation and/or tortuosity.
Keywords: retinopathy of prematurity